Political Economy, Alexander Von Humboldt, and Mexico’s 1810 and 1910 Revolutions - Richard Weiner (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2010)
This article, which is informed by Steve Pincus’ scholarship on revolution, engages in the novelendeavor of comparing Mexico’s 1810 and 1910 Revolutions. The article explores broad parallelsbetween the two upheavals, and highlights significant features of Mexico’s Revolutions thatscholars have ignored. Alexander von Humboldt’s Ensayo político sobre el reino de la NuevaEspaña proved to be influential in both of Mexico’s Revolutions, albeit in distinct ways in eachcase. Conflicts over political economy were also central aspects of each Revolution. Theseeconomic disagreements sometimes pitted revolutionists against traditionalists, and sometimesdivided revolutionists against each other. Even if revolutionists differed in terms of economicvisions, they were all “statists” in the sense that they designated an important role for governmentin fostering economic and social modernization.